De forensische wetenschap in Nederland (1800-1930): een terreinverkenning - Ruberg, Willemijn; Dijkstra, Nathanje (Studium, 2016)
Forensic science in the Netherlands (1800-1930): an explorationFocusing on the forensic culture of the Netherlands in the nineteenth and twentieth centuries, this article argues that historians of Dutch forensic medicine should go beyond institutional analyses of legal changes, and pay more attention to the practices of forensic medicine, psychiatry and criminalistics. During the nineteenth century, many doctors complained about the miserable state of Dutch forensic medicine. Several developments in the period 1910-1930, such as changes in the law that allocated more room for scientific expertise in the judicial process, played a pivotal role in the establishment of forensic science. Importantly, the field of criminalistics was designed and expanded by ‘the Dutch Sherlock Holmes’, the chemist dr. Co van Ledden Hulsebosch (1877-1952), who assisted the police in their investigation and was often called in by the courts as expert witness. He embodied a strict positivism, claiming to reveal the objective truth by studying objects and traces, the ‘silent witnesses’. At the same time, based on a study of court records, as well as journal and newspaper articles, this article shows that in practice the impact of scientific expertise in court differed. Criminalists professed other ideals of objectivity than psychiatrists and doctors.